# NCTB Class 7 Math Chapter Four Exercise 4.3 Solution

NCTB Class 7 Math Chapter Four Exercise 4.3 Solution by Math Expert. Bangladesh Board Class 7 Math Solution Chapter 4.3 “Multiplication & Division of Algebraic Expressions” Exercise 4.3 Solution.

 Board NCTB Class 7 Subject Math Chapter 4.3 Chapter Name “Multiplication & Division of Algebraic Expressions” Exercise 4.3 Solution

## Exercise:- 4.3

(1) Solution:- 3a2 b x (-4ab2)

= – 12 a3 b3 (d)

(2) Solution:- 20 a6b3/4a3 b

= 5 a3 b3(c)

(3) Solution:-  – 25x3 y/ 5xy3

= -5x2/y2

(4) Solution:- (8a-2b) + (7a+4b)

= (8×3-2×2) + (-7×3+4×2)

= (24-4) + (-21+8)

= 20-13

= 7.

(5) Solution:- x3+2x2-1

= (-1)3 +{2x (-1)2}

= -1+2-1

= 0

(6) Solution:- 10x6 y5 z4/-5×2 y2 z2

= -2x4 y3 z2

(7) Solution:- (a)  (i) & (ii) are correct.

(8) Solution:- ( mx)y

= (m3)2

(9) Solution:- a0= 1 (c)

(10) Solution:- x7/x-2

= x9 (a)

(11) Solution:- x- {x- (x-y)}

= x- (x-x +y)

= x-y (c)

(12) Solution:- (x +y) x [x-{x-9x-y)}]

= (x +y) x (x-y)

= x2– y2 (d)

(13) Solution:- a5 x (-a3)0 x a-5

= -a5+3-5

= -a3 (d)

(14) Solution:- [2-{(1+1)-2}]

= 2-{2-2}

= 2

(15) Solution:- 7+2[-8-{-3-(-2-3)}-4]

= 7+2[-8-{-3+5}-4]

= 7+2[-8-2-4]

= 7+2[-14]

= 7-28

= -21

(16) Solution:- -5-[-8-{-4-(-2-3)}+13

= -5-[-8-{-4+5}+13

= -5-[-8-1+13]

=-5-4

= -9

(17) Solution:- 7-2 [-6+3(-5+2(4-3)}]

= 7-2 [-6+3{-5+2×1}]

= 7-2[-6+3x-3]

= 7-2 [-6-9]

= 7-2 (-15)

= 7+30

= 37

(18) Solution:- x-{a+ (y-b)}

= x-(a +y-b)

= x-a-y +b

(19) Solution:- 3x+(4y-z) – {a-b- (2c-4a) -5a}

= 3x+4y-z[a-b-2c+4a-5a}

= 3x+4y-z-[-b-2c]

= 3x+4y-z+b+2c

(20) solution:- -a-[-3b-{-2a-(-a-4b)}]

= -a-[-3b-{-2a+a+4b}]

= -a-[-3b-{-2a+a+4b}]

= -a-{-3b+a-4b}

= -a-{-7b+a}

= 7b-2a

(22) Solution:- {2a-(3b-5c)}-[a-{2b-(c-4a)}-7c]

= {2a-3b+5c}- [a-[2b-c+4a}-7c]

= 2a-3b+5c- [a-2b+c-4a-7c]

= 2a-3b+5c-[-3a-2b-6c]

= 2a-3b+5c+3a+2b+6c

= 5a-b+11c

(23) Solution:- -a+[-6b-{-15c+(-3a-9b-13c)}]

= -a+[-6b-{-15c-3a-9b-13c}]

= -a+[-6b-{-28c-3a-9b}]

= -a+[6b+28c+3a+3b]

= -a+3b+28c+3a

= 2a+3b+28c

(24) Solution:- -2x-[-4y-{-6z-(8x-10y+12z)}]

= -2x-[-4y-{-6z-8x+10y-12z}]

= -2x-[-4y-{-18z-8z-8z-8x+10y}]

= -2x-[-4y+18z+8x-10y]

= -2x-[-14+18z+8x]

= -2x+14y+18z+8x

= -10x+14y-10z

(27) Solution:- 20 –[{( 6a+3b) – (5a-2b)}+6]

= 20-[{(6a+3b-5a+2b}+6]

= 20-[{a+5b}+6]

= 20-[a+5b+6]

= 20-a-5b-6

= 14-a-5b

(29) Solution:-  15a+2[3b+3(2a+2(2a+b)}]

= 15a+2[3b+3 (2a+4 a-2b)}]

= 15a + 2[3b+3 (2a-4 a-2b)}]

= 15a+2[3b-6a-6b]

= 15a+2[-3b-6a]

= 15a-6b-12a

= 3a-6b

(29) Solution:- [8b-3{2a-3(2b+5)-5(b-3)}]-3b

= [8b-3{2a-6b-15-5b+15}]-3b

= [8b-3{2a-11b}]-3b

= [8b-6a+33b]-3b

= 41b-6a3b

= 38b-6a

(30) Solution:- a-b +c-d

= a- (b-c+ d)

(31) Solution:-  a-b-c +d-m +n-x +y

= a-(b +c-d)-m+ (n-x) +y

(32) Solution:- 7x-5y+8z-9

1st, 7x-5y- (-8z+9)

2nd, 7x+{-5y-(-8z+9)}

Therefore, 7x+{-5y-(-8z+9)}

(33) Solution:- (a) (15x2+7x-2)- (5x-1)

= 15x2+7x-2-5x+1

= 15x2+2x-1

(b) (15x2+7x-2) x (5x-1)

= 75x3+35x2-10x-15x2-7x+2

= 75x3+20x2-17x+2

(34) Solution:- (a) A+B

= (x2-xy+y2) + (x2+xy+y2)

= (x2-xy+y2+x2+xy+y2)

= (2x2+2y2)

= 2 (x2+y2)

(b) Solution:- A x B

=  (x2-xy+y2) x (x2+xy+y2)

= x4-x3 y+x2 y2+x3y-x2 y2+xy3+ x2 y2– xy3+y4

= (x4+ x2 y2+y4)

Updated: December 16, 2020 — 6:28 am